Acute Abdomen Secondary to Ruptured Epithelial Ovarian Cancer during Pregnancy: The Relevance of Teamwork - Ortiz-Mendoza,Carlos Manuel (2017)
Abstract Acute abdomen secondary to epithelial ovarian cancer rupture during pregnancy is a rare event. Our aim is to present how the work of a coordinated multidisciplinary team in a case of ruptured epithelial ovarian cancer during pregnancy is feasible to obtain the best results possible. A 34-year-old woman during the 37th week of her first gestation presented with an acute abdomen. During laparotomy, a ruptured 16.5-cm left ovarian tumor was detected; the tumor was extirpated and sent to pathologic evaluation. In the meantime, a Kerr cesarean section was performed, and a healthy female neonate was born. The tumor was diagnosed as a cystadenocarcinoma; therefore, the family and the combined surgical team (obstetricians and a surgical oncologist) decided to complete a definitive radical ovarian cancer surgery: hysterectomy, right salpingooophorectomy, lymphadenectomy, omentectomy and appendectomy. The patient’s postoperative evolution was uneventful, and she was sent to adjuvant chemotherapy.